2021
DOI: 10.3390/md19010022
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Biosynthesized Silver Nanoparticles and Natural Phenolic Compounds against Drug-Resistant Fish Pathogens and Their Cytotoxicity: An In Vitro Study

Abstract: Fish pathogens causing disease outbreaks represent a major threat to aquaculture industry and food security. The aim of the presented study is to develop safe and effective bioactive agents against two bacterial isolates: Aeromonas hydrophila and Pseudomonas fluorescens. We employed a broth microdilution method to investigate the antibacterial effect of biosynthesized silver nanoparticles (AgNPs); rutin, a natural flavonoid extracted from Ruta graveneoles; and heliomycin, a secondary metabolite produced by mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…erefore, the present review aimed to show the synergistic effects of rutin with anticancer drugs in cancer cell lines (Table 2). Rutin was demonstrated to target various inflammatory, apoptotic, autophagic, and angiogenic signalling mediators, including nuclear factor-κB, tumor necrosis factor-α, interleukins, light chain 3/Beclin, B cell lymphoma 2 (Bcl-2), Bcl-2 associated X protein, caspases, and vascular endothelial growth factor [40,81]. A critical analysis of the anticancer potential of rutin and associated molecular targets among various cancer types has not been performed previously.…”
Section: Rutin In Combination With Chemotherapy Drugs: In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, the present review aimed to show the synergistic effects of rutin with anticancer drugs in cancer cell lines (Table 2). Rutin was demonstrated to target various inflammatory, apoptotic, autophagic, and angiogenic signalling mediators, including nuclear factor-κB, tumor necrosis factor-α, interleukins, light chain 3/Beclin, B cell lymphoma 2 (Bcl-2), Bcl-2 associated X protein, caspases, and vascular endothelial growth factor [40,81]. A critical analysis of the anticancer potential of rutin and associated molecular targets among various cancer types has not been performed previously.…”
Section: Rutin In Combination With Chemotherapy Drugs: In Vitromentioning
confidence: 99%
“…A critical analysis of the anticancer potential of rutin and associated molecular targets among various cancer types has not been performed previously. Moreover, combination therapy can lead to a decrease in drug resistance and chemotherapeutic side effects [40,[78][79][80][81][82]. 6…”
Section: Rutin In Combination With Chemotherapy Drugs: In Vitromentioning
confidence: 99%
“…The findings of our study are in accordance with previously reported research by Eram et al [ 58 ]. Nanoparticles show better bioactivities and safety when used synergistically with plant extracts due to the fabrication of bioactive phytochemicals on their surface [ 59 , 60 , 61 ]. In this study, we have also found that synergistic solution of CaONPs and CCFE show less toxicity and enhanced bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations of our study, our findings of the synergistic effects of the two synthesised nanoparticles when combined seem to support some earlier reports of improved antimicrobial effects by combinations of AgNPs with tomato, onion, acacia, neem, Eucalyptus globulus, Trichophyton rubrum , or garlic ( 57 61 ). One study that combined AgNPs synthesised with the rutin flavonoid and heliomycin antibiotic reported dose-dependent and synergistic antibacterial activity against Aeromonas hydrophila and Pseudomonas fluorescens ( 62 ).…”
Section: Discussionmentioning
confidence: 99%